1983
DOI: 10.1002/pol.1983.180211205
|View full text |Cite
|
Sign up to set email alerts
|

Birefringence and glass transition temperatures of poly(diethylene glycol terephthalate) networks

Abstract: SynopsisA series of polymer networks were prepared by txifunctionally endlinking poly(diethy1ene glycol terephthalate). The elastomeric properties of these materials were studied at constant temperature using experiments that involve both the elastic force and birefringence. Whereas the stress-strain isotherms show an anomalous increase in the modulus a t very high elongation ratios, a downturn appears in the birefringence-strain isotherms at the same extensibilities. These results suggest that the upturn that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

1984
1984
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…It should be pointed out that the networks are amorphous and they apparently do not crystallize under elongation. A similar behavior was found in poly(diethylene glycol terephthalate) networks 13. Dielectric Measurements.…”
supporting
confidence: 74%
See 1 more Smart Citation
“…It should be pointed out that the networks are amorphous and they apparently do not crystallize under elongation. A similar behavior was found in poly(diethylene glycol terephthalate) networks 13. Dielectric Measurements.…”
supporting
confidence: 74%
“…On the contrary, gauche states about O-CH2 bonds of both the ester group and the ether groups of the glycol residue have energies 0.3 and 0.9 kcal mol'1, respectively, above those of the respective trans states. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] The values reported for the energy of gauche states about CH2~C*0* bonds, E"a, vary in the range 1.2-0 (or below) kcal mol"1, with respect to that of the alternative trans states.3"9 Moreover, gauche states about CH2-CH2 bonds, which cause first-order CH2...OO* interactions, have energies lying in the range 0.3-0.7 kcal mol'1 above that of the corresponding trans states.3-20 Finally, gauche states about the CH2CH2-CH2CH2 bonds are disfavored by ca. 0.5 kcal mol"1 with respect to the trans states.…”
Section: Discussionmentioning
confidence: 99%
“…There have been several investigations of the effect of mechanical strain on the segmental dynamics of polymers, using dynamic mechanical and broadband dielectric spectroscopies. In single phase elastomers, strain has been observed to have no effect, , to speed up, or to slow down , segmental relaxation, with even a nonmonotonic response to strain reported . These effects have been rationalized in terms of two competing effects: the decrease of configurational entropy due to chain orientation leading to longer relaxation times, and a small decrease of density (due to the small, but finite compressibility) tending to speed up the dynamics.…”
Section: Resultsmentioning
confidence: 99%
“…35−39 In single phase elastomers, strain has been observed to have no effect, 34,37 to speed up, 32 or to slow down 35,36 segmental relaxation, with even a nonmonotonic response to strain reported. 33 These effects have been rationalized in terms of two competing effects: the decrease of configurational entropy due to chain orientation leading to longer relaxation times, and a small decrease of density (due to the small, but finite compressibility) tending to speed up the dynamics. However, these effects are generally small, if observed at all, corresponding to changes of the glass transition temperature of a few degrees or less.…”
Section: δηmentioning
confidence: 99%
“…The values of A3 and A3', shown in columns six and seven of this In order to investigate whether crystallinity vestiges were developed in the networks under strain, which might be responsible of the high value of the modulus, studies on the birefringence of the networks were recently made. 30 It was found that the stress-optical coefficient, C, decreases with increasing strain, suggesting that crystallinity is not developed in the strained networks. Moreover, the appearance of a downturn in the value of C for values of a at which an upturn in the plots of Figure 1 appears suggests that these upturns are not due to crystallinity but to maximum chain extensibility.…”
Section: Resultsmentioning
confidence: 99%